Melatonin regulates the periodic growth of secondary hair follicles through the nuclear receptor RORα - Lu, Zeyu; Wu, Jing; Wu, Jing; Zhang, Tiejia; Liu, Junyang; Mu, Qing; Terigele,; Wu, Zixian; Zhang, Yanjun; Su, Rui; Liu, Zhihong; Wang, Zhiying; et al. (Frontiers in Veterinary Science, 2023)
Cashmere is the fine bottom hair produced by the secondary hair follicles of the skin. This hair is economically important. Previous studies by our research group have shown that exogenous melatonin (MT) can regulate the periodic growth of secondary hair follicles, induce the secondary development of villi, and alter the expression of some genes related to hair follicle development. Few studies on the regulation of villus growth by MT binding receptors have been published. In this study, MT was implanted subcutaneously behind the ear of Inner Mongolia cashmere goats. RT-qPCR, in situ hybridization, Western blot analysis, immunofluorescence and RNAi techniques were used to investigate the receptors and functions of MT in regulating the development of secondary hair follicles in Inner Mongolia cashmere goats. The results showed that MT binds to the nuclear receptor RORα on dermal papilla stimulates hair follicle development and promotes villus growth. The RORα mRNA expression in the skin of Inner Mongolia cashmere goats was periodic and showed a trend of first increasing and then decreasing. The expression began to increase in February, peaked in April, and reached the lowest level in May. RORα significantly affected the mRNA expression of β-catenin gene, a key gene in hair follicle development, in the presence of MT. It will lay a solid molecular foundation for further research on the regulation mechanism between MT receptor and villus growth and development and to achieve artificial regulation of villus growth time and yield to improve the effect of villus production.